Study of heat deformation influence in surface strain hardening of steel by thermofriction processing - Volkov Оleg (Eastern-European Journal of Enterprise Technologies, 2016)
The paper deals with studying the heat deformation influence in the surface strain hardening of steels by thermofriction processing. The main objective of the work was to determine the relationship between the surface heating temperature during TFP, cooling rate, deformation, structure formation and properties of steels, hardened by TFP. The study solved the thermal conductivity problem, which allowed determining the surface heating temperature of samples of steels 15Kh11MF, 65G, U8A, Kh12M in TFP. The photographs of microstructures, which show changes over the cross section of the samples are presented. The presence of surface-hardened “white layer” with increased hardness is obvious, as evidenced by the prints of micro-hardness measurements. The data showed that the deformation mechanism of hardening in a short-term heating of the hardenable surface is predominant in TFP. It is also noted that the “deformed grained martensite” structure is formed, the hardness of which is more than twice the hardness of the martensite structure obtained in hardening of the proposed steels and can be considered as a type of nanostructure.